Myeloid-derived suppressor cells and pulmonary hypertension - Zhang, Hui; Li, Qi-Wei; Li, Yuan-Yuan; Tang, Xue; Gu, Ling; Liu, Han-Min (Frontiers in Immunology, 2023)
Pulmonary hypertension (PH) is a chronic pulmonary vascular disorder characterized by an increase in pulmonary vascular resistance and pulmonary arterial pressure. The detailed molecular mechanisms remain unclear. In recent decades, increasing evidence shows that altered immune microenvironment, comprised of immune cells, mesenchymal cells, extra-cellular matrix and signaling molecules, might induce the development of PH. Myeloid-derived suppressor cells (MDSCs) have been proposed over 30 years, and the functional importance of MDSCs in the immune system is appreciated recently. MDSCs are a heterogeneous group of cells that expand during cancer, chronic inflammation and infection, which have a remarkable ability to suppress T-cell responses and may exacerbate the development of diseases. Thus, targeting MDSCs has become a novel strategy to overcome immune evasion, especially in tumor immunotherapy. Nowadays, severe PH is accepted as a cancer-like disease, and MDSCs are closely related to the development and prognosis of PH. Here, we review the relationship between MDSCs and PH with respect to immune cells, cytokines, chemokines and metabolism, hoping that the key therapeutic targets of MDSCs can be identified in the treatment of PH, especially in severe PH.